Improved early-warning estimates of luminosity distance and orbital inclination of compact binary mergers using higher modes of gravitational radiation. Issue 3 (28th March 2022) - Singh, Mukesh Kumar; , Divyajyoti; Kapadia, Shasvath J; Shaikh, Md Arif; Ajith, Parameswaran
ABSTRACT: The pre-merger (early-warning) gravitational-wave (GW) detection and localization of a compact binary merger would enable astronomers to capture potential electromagnetic (EM) emissions around the time of the merger, thus shedding light on the complex physics of the merger. While early detection and sky localization are of primary importance to the multimessenger follow-up, improved estimates of luminosity distance and orbital inclination could also provide insights on the observability of EM emission. In this work, we demonstrate that the inclusion of higher modes of gravitational radiation, which vibrate at higher multiples of the orbital frequency than the dominant mode, would significantly improve the early-warning estimates of the luminosity distance and orbital inclination of asymmetric compact binaries, in particular, neutron-star black hole mergers. This will help astronomers to better determine their follow-up strategy of such systems. Focusing on future observing runs of the ground-based GW detectors, we show that for neutron-star black hole binaries that are potentially EM-bright, the inclusion of higher modes improves the luminosity distance estimates by a factor of ∼1 − 1.5 (1.1 − 2) [1.1 − 5] for the O5 ( Voyager ) [3G] observing scenario, 45 (45) [300] s before the merger. There are significant improvements in orbital inclination estimates as well. We also investigate these improvements with varying sky-location and polarization angle. Combining the luminosity distance uncertainties with localization skyarea estimates, we find that the number of galaxies within localization volume is reduced by a factor of ∼1 − 2.5 (1.2 − 4) [1.2 − 10] with the inclusion of higher modes in O5 ( Voyager ) [3G].